PERBAIKAN KERUSAKAN REMOTE CONTROL SYSTEM UNIT (RSCU) PADA PERALATAN DVOR (DOPPLER VHF OMNIDIRECTIONAL RANGE) STUDI KASUS BANDARA AHMAD YANI SEMARANG - Mutiara Widasari Sitopu (Jurnal Penelitian)
DVOR (Doppler VHF Omnidirectional Range) equipment is used by pilots as a navigation aid when the plane is about to land at the destination airport. DVOR is an air navigation equipment to guide aircraft in order to land perfectly at the destination airport, where the equipment functions to provide information in the form of azimuth, bearing in the frequency range of 108 MHz - 118 MHz using the Doppler effect. If the DVOR equipment in the form of a remote control system unit (RSCU) is damaged, it will prevent the aircraft from landing because there is no guide that can be used by the pilot. In this study, we succeeded in analyzing the damage to the remote control system unit on DVOR equipment by resetting the radio link on the antenna and on the laptop so that it can function as expected.